Near electromagnetic fields in medical and radar imaging - Thiyagarajah Sudharshan Naveendra. (2008)
This thesis addresses the impact of the near electromagnetic fields in the areas of Radar imaging, biomedical imaging and signal processing. In Radar imaging the conventional point scatterer model is replaced by a collection of infinitesimal electric dipole model which is used to formulate a near-field electromagnetic signal model for image synthesis. Two new factors, namely a Magnitude Modifying Factor and a Phase Modifying Factor have been introduced. An algorithm to perform imaging in the near field region has been proposed and the inherent image intensity artifacts have been removed by incorporating the two aforementioned factors. The corrected image domain data is shown to yield accurate Radar images in the near field region.